O fenômeno esporte na formação profissional no Curso de Licenciatura em Educação Física: saberes e dilemas para a prática pedagógica - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
This study should be carried out in the field of vocational training. The research is qualitative with descriptive methodological design. The central question of the research is to answer: How does the process of teaching in the professional formation in the course of Degree in Education? The objectives of the research are: a) To analyze the teaching process in vocational training in the degree course in Education. b) Challenge of the academic formation and of the masters in Physical Education in relation to the teaching of the sports disciplines in the professional formation; c) to verify an organization delimited by the teachers of the sports disciplines that are part of the curriculum of the Degree of Physical Education; d) Indicate the indicators on the sport, while the multicultural guides have access to the skills of the Licentiate Course in Physical Education, as well as the aspects that influence the professional formation; d) To identify how teachers articulate pedagogical practices in the sports disciplines as manifestations and sports modalities, from the methodological delimitations pointed to the development of the sport in the Degree of Physical Education. The present thesis assumes that, given the complexity of professional training in the Licentiate Course in Physical Education, which in many contexts is with diverse characteristics, we argue about the necessity that the professional training in the Degree in Physical Education should to prioritize, in the development of the sports disciplines, a reflexive pedagogical process, aiming at bringing the various manifestations and dimensions of the sport closer together, to an intervention model capable of articulating theory-practice-reflection in the teaching process, / or biophysiological at school. We show that the professional training in the Degree in Physical Education in many contexts represents the role of partnership of the dominant model, through the sports system, since its object of study reflects the aptitude, technique and physical training, enabling the high income or prioritizing the exclusive teaching of sports considered to have the greatest impact on society, therefore, we justify the fact that we seek subsidies to (re) think about the systematization of sports in the curricula of Higher Education Institutions. The research was carried out in two Higher Education Institutions (IES) Public in the State of Paraná (IES A, IES B). The subjects participating in the research were the professors of the sports disciplines and the academics of the 4th year of the Degree in Physical Education. The instruments used to collect data were: documentary analysis of the teaching plans of the sports subjects and the curricular matrix of the Course (IES A, IES B), semi-structured interview for teachers of the sports disciplines (IES A, IES B), questionnaire (IES A, IES B) and a focus group for IES B academics. The research methodology is embodied by the theoretical methodological assumptions of Content Analysis (BARDIN, 1977). The results of the research indicate that sport is a predominant and significant content in professional training in the Degree in Physical Education, and it is necessary to have experiences and experiences that can bring teaching practice closer to the daily life of the school, reiterating the indispensability of rigor and quality of knowledge about the sport and the reality in which it will be developed. In this way, we seek subsidies for the teaching action that can meet the new educational needs, generated by different positions of how to teach sports in the professional training in the Degree of Physical Education.
El fenómeno deportivo en la formación profesional en el Curso de Licenciado en Educación Física:saber y dilemas para la práctica pedagógica
Keywords: Formação profissional; Esporte; Licenciatura em Educação Física; Professional training; Sport; Graduation in Physical Educatio; CNPQ::CIENCIAS HUMANAS::EDUCACAO